Comparison of the kinematic features between the in vivo active and passive flexion-extension of the subaxial cervical spine and their biomechanical implications. - Hsu WH; Chen YL; Lui TN; Chen TY; Hsu YH; Lin CL; Ming-Lun T; Hsu, Wen-Hsing; Chen, Yao-Liang; Lui, Tai-Ngar; Chen, Tzu-Yung; Hsu, Yung-Hsin; et al. (Spine (03622436))
Study Design: An in vivo motion analysis of active and passive kinematic cervical flexion-extension. Objective: The study was aimed at investigating the differences between the active and passive kinematic sagittal motions of the subaxial cervical spine. Summary Of Background Data: The biomechanical behavior of the cadaver spinal column is different from that of the in vivo spine. Two major issues were concerned: the complex neuromuscular control of the in vivo cervical spinal motion and the unknown true nature of the passive cervical spinal motion. The kinematic characteristics of active and passive spinal motions need to be clarified. Methods: The active and passive motion patterns of the subaxial spine in the sagittal plane were recorded by digital video fluoroscopy. The motion of functional units from C3-C4 to C6-C7 of the cervical spine were processed using Image J, an image processing software, in both active and passive cervical motions. The Cobb's angle was measured in serial flexion and extension motions, and a comparison of this angle in both active and passive motions was made in 12 patients with degenerative disc herniation. Results: The difference between active and passive gentle flexion was minimal, and the degree of their correlation was high. The differences in the degree of gentle extension between active and passive motion were variable, and their correlation was low. During early passive flexion, the degree of flexion at the upper level was less and that at the lower level was more as compared to that observed at the respective levels in early active flexion. Conclusion: In gentle flexion, the active and passive cervical spinal motions are closely approximated, which implies that the active neuromuscular control mainly plays the buffer-and-brake mechanism without placing additional load on the spine. In contrast, the degree of passive extension is limited, and active neuromuscular control may place additional load on the spine.